Sociologies and the discursive power of religions. - Zavala Pelayo, Edgar (El Colegio de Mexico, A.C. : El Colegio de México, 2020)
"This book is about the counter-intuitive, awkward influence of religion on sociology in Mexico. More generally though, this is a book about societies in different world religions that strive for secularism on the one hand, and yet on the other hand may blend their most revered scientific rationalities with not onlu their pressing moral concerns, but also their most deeply held beliefs. The books offers no prescription for disentangling these apparently incompatible ways of knowing; it instead invites readers to challenge the acepted narratives, and to rethink the taken-for-granted secularism of the social sciences."--Publisher.